Posterior reversible encephalopathy syndrome following Miller-Fisher syndrome. Issue 7 (15th July 2021) - Bernardes, Catarina; Silva, Cristiana; Santo, Gustavo; Correia, Inês
Abstract : A 71-year-old woman presented to the emergency room with dysphonia, diplopia, dysphagia and generalised weakness since that day. Neurological examination revealed eye adduction limitation, ptosis, hypoactive reflexes and gait ataxia. Blood and cerebrospinal fluid analysis and brain CT were normal. Electromyography revealed a sensory axonal polyneuropathy. She was diagnosed with Miller-Fisher syndrome (MFS) and started on intravenous immunoglobulin. Two days after intravenous immunoglobulin treatment was completed, she developed a sustained hypertensive profile and presented a generalised tonic-clonic seizure. Brain MRI was suggestive of posterior reversible encephalopathy syndrome (PRES) and supportive treatment was implemented with progressive improvement. PRES may be a possible complication of MFS not only due to autonomic and inflammatory dysfunctions, but also as a consequence of its treatment. Patients with MFS should be maintained under close surveillance, especially in the first days and preferably in intermediate care units.